Assessment of mediated interactivity within the scope of the Anthropological Theory of Didactics Valoración de la interactividad mediada en el ámbito de la Teoría Antropológica de la Didáctica - Ospina Marulanda, Liliana Patricia; Delgado García, César Augusto (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract We present progress made in doctoral thesis «Configuration of the assessment practices of mathematics teachers at university». Preliminary analysis shows the predominance of «summative assessment» of learning, content-centered, aside from the teaching and study activities, producing poor operative learning outcomes. This didactic phenomenon entails the problem of establishing the conditions and constraints that hinder the development of a more functional kind of assessment that mediates these activities and obtain more operational learning. Finally, we construct the concept of assessment of mediated interactivity as a contribution to the design and management of didactic and mathematical praxeology. Resumen Presentamos los avances de la tesis doctoral: «Configuración de las prácticas evaluativas de los profesores de matemáticas en la universidad». Los análisis preliminares ponen de manifiesto el predominio de la «evaluación sumativa», centrada en contenidos, al margen de las actividades de enseñar y estudiar, produciendo aprendizajes poco operativos. Este fenómeno didáctico conduce a plantear el problema de establecer las condiciones y restricciones que dificultan o impiden el desarrollo de una evaluación más funcional, que medie en dichas actividades y logre aprendizajes más operativos. Finalmente, construimos el concepto de evaluación de la interactividad mediada como aporte al diseño de praxeologías didácticas y matemáticas.